Comparison of the endocytoscopic and clinicopathologic features of colorectal neoplasms - Takeda, Kenichi; Kudo, Shin-ei; Misawa, Masashi; Mori, Yuichi; Kudo, Toyoki; Kodama, Kenta; Wakamura, Kunihiko; Miyachi, Hideyuki; Hidaka, Eiji; Ishida, Fumio; Inoue, Haruhiro (Endoscopy International Open, 2016)
Background and aim: Permeation of a vein or lymphatic vessel by a tumor is a key risk factor for lymph node metastasis. We examined the features of colorectal tumor vessel permeation using endocytoscopy, an ultra-high magnifying endoscopic system combined with a narrow-band imaging capability (EC-NBI).Patients and methods: We examined 188 colorectal lesions using EC-NBI before treatment was started. We measured the diameters of tumor vessels on EC-NBI images. We used the tumor vessel diameter (the mean diameter of four tumor-associated vessels) and the variation in tumor vessel caliber (the difference between the maximum and minimum diameters of the vessels expressed as a proportion) to judge changes in vessel formation. We examined the relationship between these variables and the extent of venous or lymphatic vessel permeation (vessel invasion) established by immunohistochemical examination of the resected specimen using monoclonal antibodies against the CD34 and D2 – 40 antigens. We also analyzed the relationships between tumor vessel diameter, tumor vessel caliber variation, and depth of tumor invasion.Results: There were significant differences in tumor vessel diameter and caliber variation between tumors in situ and T1 – T3 carcinomas. In T1 carcinomas, larger tumor vessel diameter and greater tumor vessel caliber variation were significantly associated with venous permeation. In T2 and T3 carcinomas, greater tumor vessel caliber variation was significantly associated with venous permeation.Conclusions: The vessel diameter and caliber variation of colorectal tumor microvasculature are associated with depth of invasion and venous permeation, especially in T1 carcinomas.